Pengaruh Penggunaan Media Pembelajaran Padlet terhadap Minat Belajar Siswa pada Mata Pelajaran Sejarah Kelas XI di SMA Negeri 5 Pontianak - Lia Apriyani; Astrini Eka Putri; Mohammad Rikaz Prabowo (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to determine the effect of using Padlet media on students’ learning interest. The background of this research stems from the low level of students’ learning interest caused by learning activities that are still conventional and lack student engagement. Padlet media was chosen because it has interactive features that can increase student participation and learning motivation. This study employed a quasi-experimental method with a non-equivalent control group design. The instrument used was a student learning interest questionnaire consisting of 30 statement items using a 1–5 Likert scale. The data were analyzed using a normality test, homogeneity test, independent t-test, and effect size analysis (Cohen’s d) to determine the level of significance and the magnitude of the treatment effect. The results showed that the average pretest score was 38.76, while the posttest score was 54.01. The results of the independent t-test indicated a Sig. (2-tailed) value of 0.009 < 0.05, which signifies a significant difference before and after the treatment. In addition, the effect size value of 0.77 falls into the moderate category. Therefore, it can be concluded that the use of Padlet media has a significant effect on increasing students’ learning interest.